Pengaruh efikasi diri dan motivasi belajar terhadap kemandirian belajar siswa akuntansi kelas X SMK Negeri 1 Medan - Miranda, Tengku; Zainal, Andri; Darma, Jufri; Silalahi, Sondang Aida; Nurhayani, Ulfa (Universitas Negeri Surabaya, 2024)
This study aims to examine the effect of self-efficacy and learning motivation on learning independence in basic accounting equation material. The population was 140 students of class X AKL State Vocational High School 1 Medan. The sampling technique used Simple Random Sampling which amounted to 104 students. Data collection techniques using questionnaires. The data analysis method uses PLS Algorithm and bootstrapping test with Smart PLS 4.1.0.1. Based on the results of the study, it can be concluded that self-efficacy and learning motivation have a positive effect on learning independence. Suggestions that can be given from this research are a reference for schools and educators regarding the importance of self-efficacy and learning motivation in influencing student learning independence.